Islamic Economic Value as Geo-Economic Capital - Syarifuddin, Syarifuddin; Shakeel Shah, Hassan (IKONOMIKA, 2026)
This study investigates Surah Al-Fīl through a geo-economic framework, proposing that the Qur’anic narrative functions not only as a theological account but also as a critique of coercive economic domination. It conceptualizes sacred space as a form of strategic capital embedded within trade, legitimacy, and political authority. The research employs qualitative textual analysis of key Qur’anic terms, alam tara, kayd, tadlīl, and ṭayran abābīl, combined with interdisciplinary theoretical engagement in geo-economics and global political economy. A historical-contextual approach is used to situate the narrative within the commercial landscape of pre-Islamic Mecca. The findings indicate that pre-Islamic Mecca functioned as a sacred-commercial hub in which spiritual legitimacy, social trust, and trade networks converged. The Kaʿbah operated as a stabilizing institutional node that reduced transaction costs and reinforced regional economic integration. Abraha’s failed expedition can be interpreted as an attempted geo-economic realignment designed to redirect trade and pilgrimage flows toward an alternative center of authority. The narrative demonstrates that non-material forms of power, symbolic authority, collective legitimacy, and shared belief, can effectively constrain coercive strategies and preserve economic sovereignty. The study contributes to Qur’anic studies by introducing a geo-economic interpretive lens that highlights the embeddedness of scriptural narratives within material and political realities. It advances geo-economic theory by identifying sacred capital as a strategic variable capable of shaping economic resilience and institutional stability. Furthermore, it enriches global political economy by framing spiritual legitimacy as a resilience factor within economic systems, demonstrating that sustainable influence depends not solely on material resources but also on recognized symbolic authority. Overall, the analysis underscores the enduring relevance of sacred space in shaping both historical and contemporary economic structures.